O lugar da mulher é realmente onde ela quiser? compreendendo o assédio sexual online à luz do modelo geral da agressão - Lima, Débora Cristina Nascimento de (2025)
The present study program aimed to explore the phenomenon of Online Sexual Harassment (OSH) through the General Aggression Model (GAM). In the first study, a scoping review, we identified that the literature mainly investigates the effects of OSH on the victims' mental health. Based on this, we proposed the second study, in which we validated the Online Sexual Harassment Scale. Through factor analyses: exploratory (N = 204; M_age = 25.18; SD = 17.49) and confirmatory (N = 203; M_age = 34.37; SD = 9.76), the scale was fixed into a bifactorial structure (unwanted sexual attention and gender harassment), with 11 items and showed adequate indices: (χ2/gl = 0.84, CFI = 1.00, GFI = 0.94, TLI = 1.00, RMSEA = 0.00 | 90% CI 0.00 - 0.02 |, SRMR = 0.1). In the third study, we explored the relationships between OSH, personality, and ambivalent sexism, and to testing the mediating role of ambivalent sexism in the relationship between personality and OSH. The results indicated that both factors of sexism (benevolent and hostile) mediate the relationship between personality and OSH (GFI = 0.92, CFI = 0.94, TLI = 0.93, RMSEA = 0.06 (90% CI: 0.05 - 0.06), SRMR = 0.09). Finally, in the experimental study, we tested the proximal cycle of the GAM and concluded that participants exposed to OSH content shared more content of the same type when they experienced negative emotions. Exposure to such content contributes to the ongoing normalization and perpetuation of digital violence against women.